Effect of Lump Coal Shape on Separation Efficiency of Gas-solid Fluidized Bed for Dry Coal Beneficiation. (2015) - Zhao, Yuemin; Zhang, Bo; Luo, Zhenfu; He, Jingfeng; Dong, Liang; Peng, Liping; Cai, Luhui
Abstract: Coal plays a dominant role in China's energy consumption structure. The efficient and clean utilization of coal sources has great significance to protect China's energy supply and environmental protection. Coal beneficiation is the primary technology of coal cleaning and recently, wet beneficiation of coal is the predominant method of purification in the world. However, the worldwide water shortage limits the development of wet beneficiation technologies. Then, it is urgent to develop efficient dry beneficiation theories and technologies. More than 2/3 China's coal resources are distributed in drought coal regions. In addition, China also has a large amount of low-rank coal which can be slimed easily. China needs to develop efficient dry coal beneficiation technology. In the gas-solid fluidized bed system, the shape of coal is of vital importance to the particle's sedimentation movement and it also has significant effect on the result of gravity concentration. In this essay, zingg index is cited to describe the shape of coal to distinguish the columnar particles from flaky ones, as a consequence of this, the equation of different particle's motion can be deduced. The experiment covers the columnar coal, flaky coal and lump ones; the result shows that separation efficiency for lump coal was the best, with EP reaching 0.055. As for columnar coal, the result was less satisfactory, reaching 0.11. In contrast, the distribution curve of flaky coal cannot be drawn because its shape affected the separation process.